Satisfaction with diagnosis process for gestational diabetes mellitus and risk perception among Australian women. Issue 1 (6th January 2015) - Goldstein, Rebecca F.; Gibson‐Helm, Melanie E.; Boyle, Jacqueline A.; Teede, Helena J.
Abstract: Objective: To evaluate satisfaction with diagnosis, risk perceptions, and health beliefs among women with gestational diabetes mellitus (GDM). Methods: In a cross‐sectional questionnaire‐based study, participants with GDM diagnosed after 26 weeks of pregnancy were recruited from hospital‐based services at Monash Health (Melbourne, VIC, Australia) and through newspaper advertisements between 2008 and 2010. Eligible participants—aged at least 18 years and able to read English—completed a questionnaire. Results: Among 46 women who completed the questionnaire, 38 (83%) were satisfied with the explanation of the GDM screening test and 31 (67%) felt that the results were explained well. Generally, women were satisfied with the information provided about lifestyle management (29 [81%] of 36) and medical therapy (26 [72%] of 36). Most women (41 [89%]) associated poor GDM control with perinatal complications. Additionally, many participants thought that insulin (35 [76%]) and lifestyle changes (30 [65%]) could reduce macrosomia. A total of 37 (82%) of 45 women perceived that they were at risk of future GDM, and 33 (73%) thought they had an increased risk of type 2 diabetes. Most women believed that they could change these risks (29 [64%] and 37 [82%] of 45, respectively). Conclusion: Women were largely positive about their experience of GDM diagnosis. Explanation of the screening test and provision of information could be improved. Risk perception was reasonable.